Resilience in the Sandwich Generation - Lumban Raja, Inez Monica; Viena, Yomima; Merida, Sarita Candra (JURNAL SPIRITS, 2023)
The term of Sandwich Generation has generally been applied to adultstaking care of older members of their family and their minor children at the same time. Currently, Indonesia sandwich generation is in their productive age financially and emotionally squeezed for their family and self-care issues. In this phenomenon, resilience character is formed within the individuals to take control and to develop in the midst of difficult circumstances. Resilience is viewed as a measure ofanxiety, depression, and stress reaction coping ability. The purpose of this study is to determine self-resilience in the sandwich generation. This study uses the Connor & Davidson scale (CD-RISC 25), and using a quantitative comperative descriptive analysis method an using an Independent t-test. The results of the study show a moderate level of resilience 97.2% that explains the individuals are capable of adapting and overcoming problems which are included in personal competence.